3D surface characterization and localization of anatomical landmarks - Liu, Xiang (2008)
This study presents a method for extracting anatomical landmarks on the surface from measured data by way of local shape analysis. In order to delineate the distortion of the anatomical structure’s surface, a 3D representation by differential geometry is used. The surface was scanned by a 3D non-contact laser scanner and curvatures were calculated from the acquired coordinates. The curvature maps were plotted and several manifest landmarks and structures were identified because of their pronounced curvature characteristics on the curvature maps. The accuracy and error of the curvature calculation were also studied. A novel approach of localizing anatomical landmarks was proposed. The proposed method is applied in the following clinical areas: (a) measure the angle of tibial torsion objectively and reproducibly (b) predict tibial nail length required in the surgery objectively (c) monitor the depth, area, and volume changes of ulcers on the foot and leg.